Star-by-star dynamical evolution of the physical pair of the Collinder 135 and UBC 7 open clusters - Ishchenko, Marina; Kovaleva, Dana A.; Berczik, Peter; Kharchenko, Nina V.; Piskunov, Anatoly E.; Polyachenko, Evgeny V.; Postnikova, Ekaterina; Just, Andreas; Borodina, Olga; Omarov, Chingis; Sobodar, Olexandr (Astronomy and astrophysics, 2024)
Context. In a previous paper using Gaia DR2 data, we demonstrated that the two closely situated open clusters Collinder 135 and UBC 7 might have formed together about 50 Myr ago. Aims. In this work, we performed star-by-star dynamical modelling of the evolution of the open clusters Collinder 135 and UBC 7 from their supposed initial state to their present-day state, reproducing observational distributions of members. Methods. Modelling of the Collinder 135 and UBC 7 dynamical evolution was done using the high-order parallel N-body code φ-GPU with up-to-date stellar evolution. Membership and characteristics of the clusters were acquired based on Gaia DR3 data. Results. The comparison of the present-day radial cumulative star count obtained from the N-body simulations with the current observational data gave us full consistency of the model with observational data, especially in the central 8 pc, where 80% of the stars reside. The proper motion velocity components obtained from the N-body simulations of the stars are also quite consistent with the observed distributions and error bars. Conclusions. These results show that our numerical modelling is able to reproduce the open clusters’ current complex 6D observed phase-space distributions with a high level of confidence. Thus, the model demonstrates that the hypothesis of a common origin of Collinder 135 and UBC 7 complies with present-day observational data.